2008
DOI: 10.1007/s00208-008-0312-6
|View full text |Cite
|
Sign up to set email alerts
|

Sign-changing stationary solutions and blowup for the nonlinear heat equation in a ball

Abstract: In this paper, we prove that if φ is a radially symmetric, sign-changing stationary solution of the nonlinear heat equationin the unit ball of R N , N ≥ 3, with Dirichlet boundary conditions, then the solution of (NLH) with initial value λφ blows up in finite time if |λ − 1| > 0 is sufficiently small and if α is subcritical and sufficiently close to 4/(N − 2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 25 publications
5
47
0
Order By: Relevance
“…. }, there exists a unique radial equilibrium u satisfying z (0,R) (u) = Z and u(0) > 0 (see [7]). On the other hand the proof of Theorem 1.8 shows that there exists a radial equilibrium u satisfying z (0,R) (u) = Z on the boundary of the domain of attraction of the zero solution.…”
Section: Introductionmentioning
confidence: 99%
“…. }, there exists a unique radial equilibrium u satisfying z (0,R) (u) = Z and u(0) > 0 (see [7]). On the other hand the proof of Theorem 1.8 shows that there exists a radial equilibrium u satisfying z (0,R) (u) = Z on the boundary of the domain of attraction of the zero solution.…”
Section: Introductionmentioning
confidence: 99%
“…Recall that if Ψ is radially symmetric, then so is Φ. In [1], we proved the following result which concerns values of α close to 4/(N − 2) for N ≥ 3.…”
Section: Introductionmentioning
confidence: 74%
“…The results in [1], [2], [3] show that there is a more subtle relationship between stationary solutions and blowup. More precisely, let Ψ ∈ C 0 (Ω) be a stationary solution of (1.1), i.e.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…For general solutions, not just positive solutions, the situation is different and more complicated. Indeed, in a recent paper [2] the authors have shown that for N 3 and α sufficiently close to α , G is not star-shaped around 0 (and in particular not convex). We do not know if this is true in general.…”
Section: 4)mentioning
confidence: 96%